Sistemas de informação geográfica aplicados ao cadastro urbano da cidade do Kilamba (Angola) - Ernesto, Mauro Ciro da Silva (2016)
Project Work presented as the partial requirement for obtaining a Master's degree in Geographic Information Systems and Science